Mechanochemically-generated solid state complex of C60-fullerene with tetra-(5, 7-diphenyl)calix[4]azulene, NMR, XRD and DFT studies. Issue 7 (3rd July 2018) - Schneider, Celine; Nishimura, Hidetaka; Lee, Jaehyun; Scott, Lawrence T.; Wakamiya, Atsushi; Forbes, Roy; Georghiou, Paris E.
Abstract: The synthesis of tetra-(5, 7-diphenyl)calix[4]azulene via the reaction of 5, 7-diphenylazulene with formaldehyde is described. Its solid-state supramolecular complexation with C60 produced by a grinding of the two components was evaluated by solid-state 13 C-NMR spectroscopy and X-ray powder diffraction. Gas-phase DFT studies of possible structures are reported. Abstract :